Impact of Pickering Intervention on the Stability of W1/O/W2 Double Emulsions of Relevance to Foods - Spyropoulos, Fotis (Langmuir : the ACS journal of surfaces and colloids, 2019)
Although water-in-oil-in-water (W1/O/W2) double emulsions have been associated with a spectrum of potential applications in foods, their complex microstructure is significantly unstable. Pickering stabilization, reputed for superior and longer-term interfacial stabilization when compared to surfactant-stabilized systems, could provide the opportunity to enhance double-emulsion stability. The current work presents a systematic study on the impact of progressively adopting such a Pickering intervention onto one or both interfaces of W1/O/W2 emulsions relevant to foods. A range of surfactants/emulsifiers and particles have been used at the W1/O or O/W2 interface of the W1/O/W2 microstructure and, where appropriate, cross-compared with the equivalent interfaces of simple emulsions (W/O and O/W, respectively). As the aqueous compartments of all investigated systems were not osmotically balanced (at the point of formulating/forming these), any advantages in terms of double-emulsion stability enhancement can be directly attributed to the employed particle stabilization. It is demonstrated that, although partial Pickering intervention can encourage stability (particularly if that is introduced at the inner W1/O interface), only complete Pickering stabilization of the double microstructure can ensure that the oil globule size is maintained and the internal water phase is retained over a storage period of one month